A novel rhamno-mannan exopolysaccharide isolated from biofilms of Burkholderia multivorans C1576. (26th June 2015) - Dolfi, Stefania; Sveronis, Aris; Silipo, Alba; Rizzo, Roberto; Cescutti, Paola
Abstract: Burkholderia multivorans C1576 is a Gram negative opportunistic pathogen causing serious lung infection in cystic fibrosis patients. Considering that bacteria naturally form biofilms, and exopolysaccharides are recognized as important factors for biofilm architecture set-up, B. multivorans was grown both in biofilm and in non-biofilm mode on two different media in order to compare the exopolysaccharides biosynthesized in these different experimental conditions. The exopolysaccharides produced were purified and their structure was determined resorting mainly to NMR spectroscopy, ESI mass spectrometry and gas chromatography coupled to mass spectrometry. The experimental data showed that both in biofilm and non-biofilm mode B. multivorans C1576 produced a novel exopolysaccharide having the following structure: About 50% of the 2-linked rhamnose residues are substituted on C-3 with a methyl ether group. The high percentage of deoxysugar Rha units, coupled with OMe substitutions, suggest a possible role for polymer domains with marked hydrophobic characteristics able to create exopolysaccharide junction zones favouring the stability of the biofilm matrix. Graphical abstract: Highlights: Burkholderia multivorans C1576 biofilm produced on semipermeable cellulose membranes. Identification of a novel exopolysaccharide containingd -Rha, d -Man, O–CH3 . Presence of hydrophobic domains able to stabilize the biofilm matrix.